A common lack of demographic equilibrium among tree species in Białowieża National Park (NE Poland): evidence from long‐term plots. (4th January 2016) - Brzeziecki, Bogdan; Pommerening, Arne; Miścicki, Stanisław; Drozdowski, Stanisław; Żybura, Henryk
Abstract: Questions: Does the size structure characterizing particular tree species in natural forest stands converge towards a steady state? What is the main reason for departures of observed tree size distributions from equilibrium models? What is the consequence of long‐term strict protection for the demography of tree species and the conservation of associated biota? Location: Stands of natural forest in Białowieża National Park (NE Poland) that have been under strict protection for about 90 yr. Methods: Data on recruitment, growth and mortality of approximately 10 000 trees representing 11 species (aspen, birch, alder, pine, oak, maple, ash, elm, spruce, lime and hornbeam), from seven replicated surveys of five permanent monitoring plots (total size = 15.44 ha), established in 1936, were used to derive theoretical, species‐specific equilibrium distributions as a basis for evaluating the demographic changes of the species involved. Results: Over a monitoring period of 76 yr, there were strong downward trends in the population densities of several tree species of different successional status and light requirements. A vast majority of the conspecific equilibrium curves, modelled on the basis of growth and mortality data, revealed a 'rotated sigmoid' shape when plotted in semi‐log plots. In contrast to these equilibrium curves, the observed tree size distributions of most species were unimodal, at both the beginning and the end of the study period. Departures between theoretical and observed distributions increased over time, particularly for shade‐intolerant and intermediate species. Conclusions: The populations of several tree species occurring in the Białowieża National Park are demographically unstable – a fact reflected in large and steadily increasing differences between theoretical and actual tree size distributions. The main reason for this are the insufficient recruitment rates typical of most species. Some tree species may very soon disappear almost entirely, and this will certainly lead to far‐reaching changes in the functioning of local forest communities. Among other consequences, the current demographic trends, as observed for Białowieża tree species, are very likely to have a strong effect on the long‐term survival of numerous forest organisms (such as insects, fungi, lichens, etc.), which depend, directly or indirectly, on the presence and balanced demography of particular tree species. Abstract : We developed theoretical, equilibrium tree‐size distributions to assess a degree of demographic stability of tree species, occurring in strictly protected forest stands in Białowieża National Park (NE Poland). We examine the possible reasons for the large and steadily growing departures between the steady‐state and observed distributions. We also discuss the most important community‐level implications of the long‐lasting tree demographic patterns.